STRATEGI INDONESIA DALAM MENANGANI ILLEGAL FISHING KAPAL IKAN ASING (KIA) DI PROVINSI KEPULAUAN RIAU TAHUN 2016 - 2018 - Gita Firsty Fanedli; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This paper is a study of the security strategy that explains about the strategy of the Indonesian government in dealing with Illegal fishing actions of foreign fishing vessels that occur in Indonesian waters, especially those in the Riau Islands Province. The Riau Islands are strategically positioned and face to face with the South China Sea which borders a number of countries. The losses suffered for these actions suffered losses of around 101 Trillion per year. This paper uses the perspective of Neorealism. In his view the theory of International Relations is a focus on the structure of systems, interacting units, continuity and changing systems. To bridge the problem with the hypothesis the author uses the level of analysis of the Nations. In Illegal, Unreported, and Unregulated Fishing (IUUF) actions the author uses Clausewitz's strategy theory. Strategy is related to military power and political goals. The Indonesian government's strategy in dealing with Illegal Fishing is to enter into an international agreement on the Port State Measures Agreement (PSMA), the implementation of the Law no. 45 of 2009, surveillance patrol operations and rely on sophisticated technology devices. This research proves that the Indonesian government has a strong commitment to eradicate IUUF in order to realize Indonesia as a world maritime axis country.Keywords: Illegal Fishing, Strategy, Riau Islands Province, Sinking, and Catching Foreign Fish Vessels